A Eu(iii) metal–organic framework based on anthracenyl and alkynyl conjugation as a fluorescence probe for the selective monitoring of Fe3+ and TNP. Issue 41 (21st September 2022) - Zhao, Yue; Wang, Chang-An; Li, Ji-Kun; Li, Qian-Li; Guo, Qiang; Ru, Jing; Ma, Chun-Lin; Han, Yin-Feng
Abstract : In this work, Eu-MOF has been synthesized and has excellent luminescence recognition ability for Fe 3+ and TNP with good selectivity and high sensitivity via luminescence quenching. Abstract : In this work, a luminescent metal–organic framework (Eu-MOF [Eu6 L6 (μ3 -OH)8 (H2 O)3 ]8 ·H2 O n ) was constructed by a solvothermal method with a linear organic ligand L (10-[(2-amino-4-carboxyl-phenyl)ethynyl]anthracene-9-carboxylic acid) based on anthracene and alkyne groups and using Eu 3+ as the metal center. The MOF exhibits a stable UiO-66 crystal structure, and a six-core cluster twelve-linked secondary structural unit was successfully synthesized using 2-fluorobenzoic acid as a modulator, forming a classical fcu topology. Moreover, it exhibits good chemical stability. Interestingly, Eu-MOF exhibited high selectivity and sensitive fluorescence burst properties towards Fe 3+ ions and 2, 4, 6-trinitrophenol (TNP) in DMF solution. For Fe 3+, the K SV value is 5.06 × 10 5 M −1 and the LOD value is 5.1 × 10 −7 M. For TNP, the K SV value is 1.92 × 10 4 M −1 and the LOD value is 1.93 × 10 −6 M. In addition, Eu-MOF showed good anti-interference ability and fast response. This work provides an excellent fluorescent sensor for the detection of Fe 3+ and 2, 4, 6-trinitrophenol (TNP) residues in contaminants.